The Pakistan remittance initiative and remittance flows to Pakistan - Qureshi, Javaeria A. (International Food Policy Research Institute, 2016)
This study investigates the impact of the Pakistan Remittance Initiative (PRI) on remittance flows to Pakistan. In 2009, the Government of Pakistan launched the PRI aimed at facilitating the flow of remittances sent home by non-resident Pakistanis. The PRI is comprised of multiple incentive schemes that are aimed at making remittance transfer faster, cheaper, and more convenient, and at increasing the attractiveness of formal channels of transfer relative to informal channels. I find that the PRI is associated with a significant increase in the formal remittances sent to Pakistan as well as a strong shift in the channels used for remit-tance transfer. Estimates suggest that while the PRI led to a significant reallocation of remittances away from the informal channel to the formal channel, it is not clear that it has increased the total amount of remittances received.